Underwater Acoustic Propagation using Monterey-Miami Parabolic Equation in Shallow Water Kayeli Bay Buru Distric - Lalita, Rayi Khasanah; Manik, Henry M; Brojonegoro, Irsan S (Journal of Applied Geospatial Information, 2023)
Indonesia's geographical position is an advantage compared to other countries, both in terms of geoeconomics, geopolitics and geostrategy. For this reason, it is necessary to develop and use acoustic methods to describe underwater features, carry out underwater communications or to measure oceanographic variables at sea. This research was intended to provide an analytical and visual graphical description with the aim that it can be used for various purposes both in the research, military and other marine fields, as well as to analyze the influence of sediment and different frequencies on acoustic propagation patterns in shallow waters of Kayeli Bay. This research was conducted using CTD data from Kayeli Bay, which is a body of water in Buru Regency, Maluku Province and is located between 3° 15' 55'' "“ 3° 22' 50" S and 127° 01'35" "“ 127° 01' 35 "E, using the Monterey-Miami parabolic equation method using 4 types of sediment and 3 different frequencies as model input. From the results of this research it can be concluded that the propagation of sound waves in shallow seas is greatly influenced by the type of sediment and frequenty used. Changes in acoustic impedance at the bottom of the water and within the water column can significantly influence the behavior of acoustic waves in shallow water environments, and accurate acoustic impedance data are critical for effective ray tracing modelling.